Bankruptcy Prediction Analysis Using Altman Z-Score Model on IDX Retail Companies for 2021–2023 - Lintang Pancar Oktavian; Siti Arbainah; Lardin Korawijayanti (Applied Accounting and Management Review (AAMAR), 2025)
This study analyzes the bankruptcy prediction of retail subsector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period using the Modified Altman Z-Score model. The retail sector plays a crucial role in Indonesia's economy but faces challenges such as intense competition, changing consumer behavior, and macroeconomic factors that may affect the financial stability of companies. Using a descriptive quantitative method and secondary data from annual financial reports, this study employs purposive sampling to select 22 companies as samples. The analysis results show that 16 companies fall into the healthy category, 2 into the vulnerable category, and 4 into the highly vulnerable category, with PT Yelooo Integra Datanet Tbk (YELO) recording the highest Z-Score and PT Globe Kita Terang Tbk (GLOB) the lowest. The Z-Score trend indicates fluctuations in most companies throughout the study period. In conclusion, the Modified Altman Z-Score model can serve as an effective bankruptcy prediction tool, benefiting investors in decision-making and assisting companies in improving financial performance and mitigating bankruptcy risks.